ANALYSIS OF BACTERIAL ABUNDANCE IN THE INTESTINES OF COMMON CARP Cyprinus carpio TREATED WITH THE PROBIOTIC Bacillus subtilis - Alin Shelina Nurashila; Yuniar Mulyani; Zuzy Anna; Mochamad Untung Kurnia Agung (Jurusan Perikanan dan Kelautan, 2023)
Efforts to increase microbial populations in fish intestines tract can be done by utilizing microbes in the fish's digestive tract as probiotics. The application of Bacillus subtilis in fish feed mixtures can provide better growth performance in modifying microbes in the intestines of fish. The aim of this research was to analyze the bacterial community in the intestines of Common Carp(Cyprinus carpio) that have been given probiotics from the bacteria Bacillus subtilis with metagenome sequencing using 16S rRNA through Next Generation Sequencing (NGS) technology. Common carp samples were collected from maintenance conducted with different treatments, namely control fish without probiotic administration and fish treatment with mixed feed probiotic Bacillus subtilis. This research was conducted in the Laboratory of Fisheries Biotechnology, Faculty of Fisheries and Marine Science, Padjajaran University. Then molecular identification was carried out using Illumina's NGS in Novogene, Singapore. The results of the identification of using probiotic bacteria Bacillus subtilis in Common carp(Cyprinus carpio) feed affect the bacterial community in the fish intestine. In the intestines of carp that were given probiotics, the highest abundance was Proteobacteria, Fusobacteriota, and firmicutes.The highest abundance at the genus level in both samples was domiciled by the genus Cetobacterium followed by the Sphingomonas and Aeromonas.